Spatial and diurnal Diurnal Variations of Summer Hourly Rainfall Over Three Super City Clusters in Eastern China and Their Possible Link to the Urbanization. Issue 10 (31st May 2019) - Fu, Xinshu; Yang, Xiu‐Qun; Sun, Xuguang
Abstract: Three super city clusters in eastern China, that is, Beijing‐Tianjin‐Hebei (BTH), Yangtze River Delta (YRD), and Pearl River Delta (PRD), have been developed in recent decades. The spatial and diurnal variations of summer hourly rainfall over these city clusters and their possible link to the urbanization are investigated in this study, with the Climate Prediction Center Morphing technique (CMORPH) satellite precipitation estimates at high spatial‐temporal resolutions for 2004‐2009. Although the summer rainfall in eastern China is mainly characterized by large‐scale pattern, significant regional rainfall features over the three city clusters can be clearly observed, which are related to the clustered urbanization. Large hourly rainfall intensity is found over the city clusters or downwind from them. Those regions with large hourly rainfall intensity are named as the city cluster impacted regions (CCIRs), contrast to the surrounding mountainous regions where high frequency and large amount but low hourly intensity of rainfall occur. Location and geometry of each CCIR are unique because of the distinctive geography and structures among city clusters. The CCIR situates right over YRD, but it is shifted to the downwind region with an elongated shape for BTH and a circular shape for PRD. More heavy rain but less light rain occurs over the CCIRs than the surrounding regions. Diurnal variations of light rain amount and frequency can be influenced by both mountain and urbanization, and a diurnal cycle amplitude increase related to the urbanization is detected only over the CCIR of YRD where the terrains are mostly low and flat. Key Points: Large hourly rainfall intensity is found over the city clusters of eastern China or downwind from them Those regions with large hourly rainfall intensity are named as the city cluster impacted regions (CCIRs) More heavy rain but less light rain occurs over the CCIRs than the surrounding regions